2018
DOI: 10.1093/femsle/fny188
|View full text |Cite|
|
Sign up to set email alerts
|

Dysbiosis and early mortality in zebrafish larvae exposed to subclinical concentrations of streptomycin

Abstract: Exposure to low concentrations of antibiotics found in aquatic environments can increase susceptibility to infection in adult fish due to microbiome disruption. However, little is known regarding the effect of antibiotic pollution on fish larvae. Here, we show that exposure to streptomycin, a common antibiotic used in medicine and aquaculture, disrupts the normal composition of zebrafish larvae microbiomes, significantly reducing the microbial diversity found in the fish. Exposure to streptomycin also signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 69 publications
0
29
3
Order By: Relevance
“…Interestingly, fish that were only exposed to oxytetracycline tended to show increased microbial diversity. This is not in line with current literature, in which most studies investigating antibiotics observe reduced diversity ( Navarrete et al, 2008 ; Ding and He, 2010 ; Pindling et al, 2018 ; Zhou et al, 2018a , b ). The fact that saponin (and soybean meal) increases bacterial diversity in fish is observed by others ( Bakke-McKellep et al, 2007 ; Merrifield et al, 2009 ).…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…Interestingly, fish that were only exposed to oxytetracycline tended to show increased microbial diversity. This is not in line with current literature, in which most studies investigating antibiotics observe reduced diversity ( Navarrete et al, 2008 ; Ding and He, 2010 ; Pindling et al, 2018 ; Zhou et al, 2018a , b ). The fact that saponin (and soybean meal) increases bacterial diversity in fish is observed by others ( Bakke-McKellep et al, 2007 ; Merrifield et al, 2009 ).…”
Section: Discussioncontrasting
confidence: 85%
“…In a recent review of the European scenario it was shown that the levels of antibiotic in the water can reach as high as several micrograms per liter ( Carvalho and Santos, 2016 ). These antibiotics, besides inducing antimicrobial resistance ( Gullberg et al, 2011 ; Pindling et al, 2018 ), also have an impact on the fish microbial communities of gut, skin and gills, which in turn influences fish disease susceptibility ( Navarrete et al, 2008 ; Brugman et al, 2009 ; Tacchi et al, 2015 ; Pindling et al, 2018 ; Zhou et al, 2018a , b ). For example, previously, we showed that adult zebrafish exposed to a high dose (mg/L range) of the antibiotic vancomycin showed an overgrowth of Cetobacterium somerae (a fish commensal) and displayed reduced severity of chemically induced enterocolitis, whereas fish exposed to a high dose (mg/L range) of colistin sulphate showed overgrowth of Aeromonas sp.…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, we found that triclosan did not correlate with an increase in int1, which is an important genetic marker that is linked to the horizontal transfer of antibiotic resistance in the environment [24]. This result seems to confirm that triclosan resistance is more likely to result from inherent resistance to the antimicrobial [46], since we readily observed the selection of int1 elements in microbial communities that were exposed to streptomycin and arsenic in previous studies [28,30]; or to evolve via de novo mutation in bacterial lineages [46]; or via conjugation events not linked to int1 [17]. Further investigation will be required to see whether triclosan increases conjugation or resistance to other antibiotics in surface water similarly to what was found in sediments.…”
Section: Discussioncontrasting
confidence: 58%
“…The 16S rRNA sequence data were processed, aligned, and categorized with the DADA2 pipeline version 1.8 [29] using default parameters as described in [30]. The DADA2 pipeline characterizes microbial communities by identifying the unique amplicon sequence variants (ASVs) among the 16S rRNA reads [31].…”
Section: Processing and Visualization Of 16s Rrna Sequence Datamentioning
confidence: 99%
“…Increased mortality was also observed in fish exposed to WWTP effluent waters contaminated with a mixture of chemicals, including high concentrations of antibiotics [207]. While work done on experimental models suggests that adult fish can recover from short-term exposure to antibiotic [208], recent work demonstrated that concentrations of streptomycin and tetracycline as low as 1 μg/mL could cause dysbiosis and increase mortality in more susceptible zebrafish embryos [189,209]. Other negative impacts of antibiotic exposure on animal health putatively due to the effect of antibiotics on the host microbiome include disruption of the growth cycle, and reduction in fertility [210].…”
Section: Cytotoxic Effects Of Antibiotics In the Environmentmentioning
confidence: 99%